Discrete moments models for Vlasov equations with non constant strong magnetic limit - Charles, Frédérique; Després, Bruno; Dai, Ruiyang; Hirstoaga, Sever A. (Comptes Rendus. Mécanique, 2023)
We describe the structure of an original application of the method of moments to the Vlasov–Poisson system with non constant strong magnetic field in three dimensions of space. Using basis functions which are aligned with the magnetic field, one obtains a Friedrichs system where the kernel of the singular part is made explicit. A projection of the original model on this kernel yields what we call the reduced model. Basic numerical tests of the field illustrate the accuracy of our implementation. A new generating formula for Laguerre polynomials is obtained in the appendix as a byproduct of the analysis.